Stranger faces - Serpell, Namwali, 1980- (Oakland, California : Transit Books, 2020)
"If evolutionary biologists, ethical philosophers, and social media gurus are to be believed, the face is the basis for what we call "humanity." The face is considered the source of identity, truth, beauty, authenticity, and empathy. It underlies our ideas about what constitutes a human, how we relate emotionally, what is pleasing to the eye, and how we ought to treat each other. But all of this rests on a specific image of the face. We might call it the ideal face. What about the strange face, the stranger's face, the face that thwarts recognition? What do we make of the face that rides the line of legibility? In a collection of speculative essays on a few such stranger faces-the disabled face, the racially ambiguous face, the digital face, the face of the dead-Namwali Serpell probes our contemporary mythology of the face. Stranger Faces imagines a new ethics based on the perverse pleasures we take in the very mutability of faces"--
Chapter 1. Elephants in rooms. Joseph Merrick, The Autobiography of Joseph Merrick (1884) -- Chapter 2. Two-faced. Hannah Crafts, The Bondwoman's Narrative (1850s/2002) -- Chapter 3. Mop. Alfred Hitchcock, Psycho (1960) -- Chapter 4. Bear head. Werner Herzog, Grizzly Man (2005) -- Chapter 5. E-faced. The Oxford English Dictionary's Word of the Year (2015) -- Conclusion.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on November 11, 2020).
eBooks on EBSCOhost
Keywords: Merrick, Joseph Carey, -- 1862-1890.; Crafts, Hannah; Psycho (Motion picture : 1960); Grizzly man (Motion picture); Merrick, Joseph Carey, -- 1862-1890; Bondwoman's narrative (Crafts, Hannah); Psycho (Motion picture : 1960); Face -- Abnormalities; Face perception; Face in literature; Face in motion pictures; Face -- Malformations; Perception des visages; Visage dans la littérature.; Visage au cinéma.; LITERARY COLLECTIONS / Essays; Face -- Abnormalities; Face in literature; Face in motion pictures; Face perception